Facilitation skills: the catalyst for increased effectiveness in consultant practice and clinical systems leadership. Issue 2 (15th March 2017) - Manley, Kim; Titchen, Angie
ABSTRACT: Consultant practitioner is the pinnacle of the clinical career ladder for all health care disciplines in the United Kingdom. Consultant nurse, midwife and health visitor roles build on the clinical credibility and expertise characteristic of advanced level practice, but also possess expertise in: clinical systems leadership and the facilitation of culture change, learning and development; advanced consultancy approaches, and research and evaluation to prioritise person-centred, safe and effective care across patient pathways. This project aimed to help new and emerging consultants to become more effective in their role through a programme of support to develop their expertise. Emancipatory action research, supported by claims, concerns and issues tool, derived from Stakeholder Evaluation, and other methods (active learning, action learning, collaborative workshops and individual tools e.g. qualitative 360 degree feedback and reflective reviews) comprised the supportive intervention which enabled participants to research their own practice. The programme's methodology and methods helped participants to: research their own practice; theorise from practice; grow the facilitation skills needed to develop and demonstrate their own effectiveness; foster the effectiveness of others and; transform practice culture. Greater effectiveness in their multiple roles was demonstrated, as was the impact of this on others, services and organisations. The study concludes that the support programme augmented by the methodology, facilitation skills and the 10 principles derived from a concept analysis of work-based learning is central to achieving improved effectiveness and transformation of others, services and organisations. Theoretical insights at collective/community levels also resulted. Key recommendations are identified for commissioners, higher education and research.